The Translation of Proper Nouns in Victoria Aveyard’s Red Queen Novel from English to Indonesia - Shifa Nur Fadillah; Andhi Dwi Nugroho; Novita Sumarlin Putri; Johanes Climacus Setyo Karjono (Institut Agama Islam Negeri Palopo, 2023)
This study deals with the translation of proper nouns found in Red Queen novel by Victoria Aveyard into Indonesian. It aimed to (1) analyze the types of proper nouns used in the novel, (2) investigate the translation techniques used in translating the proper nouns into Indonesian, and (3) reveal the translation techniques which were dominantly used in translating the proper nouns into Indonesian. This study utilized a descriptive qualitative approach. The data in forms of words and phrases were collected using documentation technique. Then, the data dealing with the types of proper nouns were analyzed using Newmark’s theory, while those dealing with the use of translation techniques were analyzed using Molina and Albir’s theory. The result showed that there were 185 data which were divided into two types of proper nouns, namely (1) people’s names, and (2) names of object. Meanwhile, there were 9 translation techniques proposed by Molina and Albir used in translating the proper nouns, namely (1) amplification, (2) borrowing, (3) calque, (4) compensation, (5) discursive creation, (6) established equivalent, (7) linguistic amplification, (8) literal translation, and (9) reduction. Additionally, there were two dominant techniques used, namely borrowing and calque techniques.